Neonatal Programming with Sex Hormones: Effect on Expression of Dopamine d1 Receptor and Neurotransmitters Release in Nucleus Accumbens in Adult Male and Female Rats - Renard, G (Elsevier B.V., 2021)
Steroid sex hormones produce physiological effects in reproductive and non-reproductive tissues, such as the brain. In the brain, sex hormones receptors are expressed in cortical, limbic and midbrain areas modulating memory, arousal, fear and motivation between other behaviors. One neurotransmitters system regulated by sex hormones is dopamine (DA), where during adulthood, sex hormones promote neurophysiological and behavioral effects on DA systems such as tuberoinfundibular (prolactin secretion), nigrostriatal (motor circuit regulation) and mesocorticolimbic (driving of motivated behavior). However, the long-term effects induced by neonatal exposure to sex hormones on DA release induced by D1 receptor activation and its expression in nucleus accumbens (NAcc) have not been fully studied. To answer this question, neurochemical, cellular and molecular techniques were used. The data show sex differences in NAcc DA extracellular levels induced by D1 receptor activation and protein content of this receptor in male and female control rats. In addition, neonatal programming with a single dose of TP increases the NAcc protein content of D1 receptors of adult male and female rats. Our results show new evidence related with sex differences that could explain the dependence to drug of abuse in males and females, which may be associated with increased reinforcing effects of drugs of abuse. © 2021 Elsevier B.V.
Keywords: D1 receptor; Dopamine; GABA; Glutamate; Microdialysis; Nucleus accumbens; Sex hormones